How being appreciative creates change – theory in practice from health and social care in Scotland. Issue 2 (June 2018) - Sharp, Cathy; Dewar, Belinda; Barrie, Karen; Meyer, Julienne
This paper develops understanding of appreciative action research that generates curiosity and motivation as a better platform for collaborative change. Blending theory and practice it draws on the example of the My Home Life leadership programme in Scotland that explores the concepts and approaches of 'Caring Conversations' and 'playful provocation' in care homes for older people. The paper shows how they expand notions of appreciation and help people to deepen inquiry, explore values, acknowledge and express emotion without dispute or judgement, articulate tacit knowledge and give voice to things previously thought to be 'unsayable'. We explore how these generative approaches act as a powerful positive 'disruption' that brings existing relationships to life, supports a positive attitude to risk-taking and helps to devise new approaches to the local design and testing of approaches to problems. Ultimately these approaches play an important part in developing understanding of how to do appreciative action research to enhance relationships and more strengths or assets-based and collaborative ways of working and so, to develop new possibilities for changing social systems and a more future-making orientation to action research.